Sesquiterpene lactones as emerging biomolecules to cease cancer by targeting apoptosis - Hsu, Chou-Yi; Rajabi, Sadegh; Hamzeloo-Moghadam, Maryam; Kumar, Abhinav; Maresca, Marc; Ghildiyal, Pallavi (Frontiers in Pharmacology, 2024)
Apoptosis is a programmed cell death comprising two signaling cascades including the intrinsic and extrinsic pathways. This process has been shown to be involved in the therapy response of different cancer types, making it an effective target for treating cancer. Cancer has been considered a challenging issue in global health. Cancer cells possess six biological characteristics during their developmental process known as cancer hallmarks. Hallmarks of cancer include continuous growth signals, unlimited proliferation, resistance to proliferation inhibitors, apoptosis escaping, active angiogenesis, and metastasis. Sesquiterpene lactones are one of the large and diverse groups of planet-derived phytochemicals that can be used as sources for a variety of drugs. Some sesquiterpene lactones possess many biological activities such as anti-inflammatory, anti-viral, anti-microbial, anti-malarial, anticancer, anti-diabetic, and analgesic. This review article briefly overviews the intrinsic and extrinsic pathways of apoptosis and the interactions between the modulators of both pathways. Also, the present review summarizes the potential effects of sesquiterpene lactones on different modulators of the intrinsic and extrinsic pathways of apoptosis in a variety of cancer cell lines and animal models. The main purpose of the present review is to give a clear picture of the current knowledge about the pro-apoptotic effects of sesquiterpene lactones on various cancers to provide future direction in cancer therapeutics.